Recruitment Pattern for Regency Non-Permanent Employees at the Gayo Lues Regency People's Representative Council Secretariat - Gp*, Juliarman; A. Rahman, Dahlan; Wahyono, Effendi (Riwayat: Educational Journal of History and Humanities, 2024)
The recruitment pattern for non-permanent employees of the Secretariat of the People's Representative Council for Gayo Lues Regency is implemented in accordance with Law of the Republic of Indonesia Number 5 of 2014 concerning State Civil Apparatus. consisting of Civil Servants (PNS) and Government Employees with a Work Agreement (PPPK). This has been implemented since the issuance of Gayo Lues Regent Regulation Number 29 of 2018 concerning Delegation of Authority to Sign the Appointment of Regency Non-Permanent Employees within the Gayo Lues Regency Government. The aim of carrying out this research is to determine the Recruitment Pattern of Regency Non-Permanent Employees (PTTK) at the Gayo Lues Regency People's Representative Council Secretariat. This research uses a qualitative approach. This research is classified as case study research. Data collection was carried out through observation, interviews and literature study. Data analysis was carried out descriptively through the stages of data reduction, data presentation as well as conclusions and verification. The research results of the Gayo Lues Regency Government show that there are still problems with recruitment and budgeting of ASN. Non-Permanent Regency Employees (PTTK) are still needed. Budgeting can be adjusted to the financial capabilities of the Gayo Lues Regency Government. The Secretariat of the Gayo Lues Regency People's Representative Council (DPRK) is an element of administrative services and provides support for the duties and functions of the DPRK. Implementation of the duties and functions of the DPRK as well as providing and coordinating expert personnel required by the DPRK in carrying out its rights and functions in accordance with needs. In order to support the smooth running of the DPRK Secretariat's duties in facilitating the implementation of the duties and functions of the Gayo Lues DPRK, it is necessary to appoint non-permanent district employees (PTTK) for the Gayo Lues DPRK Secretariat.